Real-world insights into patients with advanced NSCLC and MET alterations. (September 2021) - Bittoni, Marisa; Yang, James Chih-Hsin; Shih, Jin-Yuan; Peled, Nir; Smit, Egbert F.; Camidge, D. Ross; Arasada, Rajeswara Rao; Oksen, Dina; Boutmy, Emmanuelle; Stroh, Christopher; Johne, Andreas; Carbone, David P.; et al.
Highlights: Patients with MET ex14 and MET amplified NSCLC differ in characteristics. Patients with MET ex14 skipping NSCLC rarely had concomitant driver alterations. Treatment patterns were heterogeneous; non-targeted treatments are commonly used. Real-world outcomes indicate that these patients have a high unmet medical need. Testing for MET alterations to identify patients that may benefit from targeted therapy is needed. Abstract: Objectives: To describe characteristics, treatment and outcomes of non-small cell lung cancer (NSCLC) patients with MET alterations ( MET exon 14 [ MET ex14] skipping or MET amplification [ MET amp]) in real-world clinical care. Methods: This non-interventional cohort study used real-world data extracted from electronic medical records from academic oncology sites in Israel, The Netherlands, Taiwan, and the USA. Patients had confirmed diagnosis of advanced (Stage IIIB–IV) NSCLC harboring MET alterations (date of diagnosis = index date) between 1 Jan 2010 and 30 Sept 2018. Medical history was assessed prior to and at the index date (baseline period), and outcomes from first date of treatment to death, loss to follow-up, or end of study period. Results: A total of 117 patients were included ( MET ex14 n = 70; MET amp n = 47); testing methods were heterogeneous. Concomitant oncogenic mutations were more common in the MET amp cohort than MET ex14. Patients in the MET ex14 cohort were older than those in MET amp, and a larger proportion were never smokers. Anticancer first-line therapies received by patients ( MET ex14; MET amp) included chemotherapy only (44%; 41%), MET inhibitors (33%; 29%), immune checkpoint inhibitor (ICI) mono-(12%; 15%) and combination-therapy (8%; 3%). Second-line therapies included chemotherapy (35%; 30%) and MET inhibitors (30%; 39%). In the MET ex14 cohort, objective response rate (ORR) was generally low (first-line 28%; second-line 30%); no patients who received ICIs had a response. In the MET amp cohort, ORR was 36% in first-line and 22% in second-line. Median (95% confidence interval) overall survival from start of first-line therapy was 12.0 months (6.8, 19.2) in the MET ex14 cohort and 22.0 months (9.8, 31.2) in MET amp. Conclusions: Heterogeneous treatments reflect the changing landscape and availability of new treatments, as well as the high unmet medical need in older, MET ex14 patients who had more advanced disease at diagnosis. MET-targeted therapies could be beneficial in patients with these rare MET alterations.